A case report of infective endocarditis in a 52-year-old female with unrepaired tricuspid atresia and d-transposition of the great arteries. Issue 4 (3rd April 2023) - Karmali, Rehan; Mazumder, Samia; Berglund, Felix; Fuchs, Margaret M
Abstract: Background: d-Transposition of the great arteries (d-TGA) is a congenital cardiac defect that is typically fatal. Those patients who survive without surgical repair and who are rare in number, need adequate intracardiac shunting and will suffer from chronic cyanosis. Here, we present a rare case of an adult with unrepaired cyanotic congenital heart disease (CHD) who developed infective endocarditis (IE) and also our approach to the medical decision-making process in this uncommonly encountered dilemma. Case summary: A 52-year-old female with unrepaired d-TGA with tricuspid atresia, hypoplastic right ventricle, unrestricted atrial septal defect, ventricular septal defect, and sub-valvular as well as valvular pulmonic stenosis with a hypoplastic, bicuspid pulmonary valve presented with abdominal pain and hypoxia and was found to have an acute renal infarct. Transthoracic echocardiogram (TTE) revealed a large mobile mass on the mitral valve. Blood cultures grew Streptococcus mitis-oralis and she was diagnosed with streptococcal native mitral valve IE complicated by a renal embolus. Her large left-sided vegetation and embolic phenomenon favoured surgery. However, a right heart catheterization showed normal intracardiac pressures, likely a result of multi-level obstruction relating to sub-valvular and valvular pulmonary stenosis protecting the pulmonary vasculature from over-circulation and pulmonary hypertension. Cardiac surgery posed a significant risk of destabilizing her delicately balanced haemodynamics. Hence, she was treated with ceftriaxone for 4 weeks. A repeat TTE 8 weeks later showed a resolution of the vegetation. Discussion: A decision for surgery vs. medical treatment for IE in adult patients with compensated CHD should be made following a multi-disciplinary assessment of each patient's unique cardiac haemodynamics and after shared decision-making with the patient.